(untitled) (Anclajes, 2022)
Aesthetics and politics were intrinsically linked during the emergence of the historical avant-gardes, but the discussion about their goals and interventions remains timely today. The intellectual field that emerged in forties and fifties Argentina, though following a moderate and seldom-disruptive version of the classic avant-garde (Sarlo 1997), did advance complex discussions on social realism and experimental forms linked more to modernism than to surrealism. In this period, Fina Warschaver (1910-1989), a writer with affiliations to Communist Party, published the controversial novel La casa Modesa (1949), which was ignored by critics due to its experimental form and its distance from the social realism promoted by communist ideology. This essay analyzes the strategies that Warschaver borrows from Virginia Woolf’s modernist approach to propose a new reading of the text that not only challenges mimesis and referential representation but also questions the naturalization of gender that limits feminine space to the domestic sphere, restricting the political action of women and censoring their artistic freedom.